Design and analysis of Contrast Enhancement of an image using DCTCS in Parallel computing environment using MATLAB - Gupta, Kunal; Madiajagan, M; Miglani, Nipunn; Agrawal, Shrivats (International Journal of Computer Sciences and Engineering, 2020)
For a wide variety of applications, image contrast enhancement is very essential. Thus, it is imperative to have a low-cost, highly efficient and quick image contrast enhancement tools. In the past image contrast enhancement has always been performed sequentially on one core. With the advent of multi-core architecture in computers, it is now possible to perform tasks concurrently which do not have task dependencies. Parallel MATLAB Toolbox is an additional functionality provided by MATLAB which utilizes the parallel capabilities of modern day computers by allowing us to resolve computationally and data-intensive problems using multicore processors, GPUs, and computer clusters. Image processing and contrast enhancement are fields which could greatly benefit from parallelization to improve performance and achieve speedup. These applications have the potential of high degree of parallelism and thus are a exceptional source for multi- core platform. Parallelization aims at taking less time and making better use of available resources for time intensive and real time jobs. This paper aims to use Parallel MATLAB Toolbox to parallelize the process of Discrete Cosine Transform and coefficient Scaling.